A Novel Strategy for the Construction of Azole Heterocycles via an Oxidative Desulfurization Approach Using Iodobenzene and Oxone® - Patel, Kavitkumar N.; Jadhav, Nikhil C.; Jagadhane, Prashant B.; Telvekar, Vikas N. (Synlett, 2012)
The oxidative desulfurization approach has been utilized for the construction of oxadiazole and thiadiazole heterocycles using iodobenzene and Oxone®. The use of iodobenzene and the inexpensive readily available oxidant Oxone® makes the reaction system simple and versatile for desulfurization.
Keywords: desulfurization; hypervalent iodine; iodobenzene; Oxone®; thiosemicarbazide; oxadiazole